Neutral silver-zinc battery positive electrode material and preparation method thereof and neutral silver-zinc battery
By introducing gold nanoclusters and Au-Ag nanoparticles into the positive electrode material of neutral silver-zinc battery, combining carbon nanotubes and melamine, the silver dissolution and agglomeration problems are solved, and the cycle stability and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202210814068.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Neutral silver-zinc batteries have problems with silver dissolution and silver nanoparticles agglomeration during the circulation process, resulting in insufficient cycle stability.
The surface-attached gold nanoclusters were formed by reacting the chloroaulic acid solution with the Ti3C2Tx solution, and then reacting with the silver nitrate and sodium citrate solutions to form a Ti3C2Tx composite with Au-Ag nanoparticles attached to the surface, and mixed with carbon nanotubes and melamine , Ti3C2Tx melamine positive electrode material with Au-Ag nanoparticles attached to the surface was prepared to inhibit silver ions migration and agglomeration.
The cycle life and rate performance of neutral silver zinc batteries are significantly improved, and the active sites of small-sized silver nanoparticles are maintained, providing ideal specific capacity and mechanical properties.
Smart Images

Figure CN115172693B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silver-zinc batteries, and in particular to a neutral silver-zinc battery positive electrode material and a preparation method thereof, and a neutral silver-zinc battery. Background Art
[0002] With the development of industrialization and the rapid consumption of fossil fuels, climate change, characterized by global warming, has occurred, which has had a serious impact on the sustainable development of human society. In order to cope with global climate change, it is necessary to develop efficient large-scale energy storage systems. Large-scale energy storage systems can effectively improve the stability of the power system during operation, alleviate regional power shortages, and enhance the overall frequency regulation capabilities of the power grid. Among the many electrochemical energy storage technologies, batteries are currently a type of energy storage technology with higher investment returns, with the characteristics of fast response speed and great commercial potential. In addition, the modular design of the battery system can achieve capacity expansion or reduction according to demand, and can form energy storage systems of different sizes within a short construction period, and can effectively reduce maintenance costs and difficulties, showing good flexibility.
[0003] As the most mature zinc-based battery, silver-zinc battery has high energy density, extremely stable output voltage and high safety, and is widely used in many fields such as aerospace, military, etc. Although the aqueous electrolyte used in silver-zinc battery can effectively solve the problem of flammability and explosion of organic electrolyte, the alkaline electrolyte used in traditional silver-zinc battery is highly corrosive to battery components, causing the active material to dissolve quickly. The dissolved silver ions will move to the negative electrode under the action of the electric field, seriously affecting the cycle stability and even the service life of the silver-zinc battery.
[0004] As a new type of silver-zinc battery, the neutral silver-zinc battery has silver or silver chloride (AgCl) as the positive electrode active material, metallic zinc as the negative electrode active material, and ZnCl2 as the electrolyte. The neutral electrolyte used in the neutral silver-zinc battery can effectively avoid the production of irreversible byproducts (ZnO), thereby improving the reversibility of the Zn negative electrode deposition / dissolution reaction. The neutral silver-zinc battery can effectively solve the problem of silver dissolution, and can improve the reversibility of the silver-zinc battery, so that the cycle stability of the neutral silver-zinc battery is greatly improved. However, due to the inherent silver dissolution and silver nanoparticle agglomeration problems of the neutral silver-zinc battery, the cycle life of the neutral silver-zinc battery is not satisfactory.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the present invention provides a neutral silver-zinc battery positive electrode material and a preparation method thereof and a neutral silver-zinc battery, aiming to solve the problem of insufficient cycle stability caused by silver dissolution and silver nanoparticle agglomeration in the existing neutral silver-zinc battery during the cycle process.
[0007] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0008] The first aspect of the present invention provides a method for preparing a neutral silver-zinc battery positive electrode material, which comprises the steps of:
[0009] Add chloroauric acid solution to Ti3C2T x The Ti3C2T with gold nanoclusters attached to the surface was obtained by reaction in solution. x Solution;
[0010] A mixed solution of silver nitrate solution and sodium citrate is added to the Ti3C2T x After the reaction, Ti3C2T with Au-Ag nanoparticles attached to the surface was obtained. x Composite materials;
[0011] The Ti3C2T x The composite material was mixed with carbon nanotube dispersion and melamine, and then vacuum filtered to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material.
[0012] Optionally, the chloroauric acid solution is added to the Ti3C2T x The Ti3C2T with gold nanoclusters attached to the surface was obtained by reaction in solution. x The solution steps include:
[0013] Add chloroauric acid solution to Ti3C2T x The solution was placed in an ice water bath and reacted under stirring to obtain Ti3C2T with gold nanoclusters attached to the surface. x Solution;
[0014] Wherein, the temperature of the ice water bath is 1°C to 15°C, and the reaction time is more than 1 hour.
[0015] Optionally, the chloroauric acid, the Ti3C2T x The mass ratio is 0.01~0.3:1.
[0016] Optionally, a mixed solution of silver nitrate solution and sodium citrate is added to the Ti3C2T x After the reaction, Ti3C2T with Au-Ag nanoparticles attached to the surface was obtained. x The steps of composite material include:
[0017] A mixed solution of silver nitrate solution and sodium citrate is added to the Ti3C2T xThe reaction was continued for more than 4 h to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x Composite materials.
[0018] Optionally, the molar ratio of the silver nitrate solution to the sodium citrate in the mixed solution of the silver nitrate solution and the sodium citrate is 1:2 to 1:7, and the molar ratio of the silver nitrate to the Ti3C2T x The mass ratio is 0.7~1.8:1.
[0019] Optionally, the Ti3C2T x The composite material was mixed with carbon nanotube dispersion and melamine, and then vacuum filtered to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x The steps of melamine cathode material include:
[0020] The Ti3C2T with Au-Ag nanoparticles attached on the surface x The carbon nanotube dispersion and melamine were added to the composite material, stirred, vacuum filtered, and dried to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material.
[0021] Optionally, the melamine is combined with a Ti3C2T2O3 substrate having Au-Ag nanoparticles attached to the surface. x The mass ratio of the composite material is 0.3-0.7:1, and the carbon nanotubes and the Ti3C2T x The mass ratio of the composite material is 0.3 to 1:1.
[0022] Optionally, the drying is specifically: drying at 60° C. to 80° C. for 12 h to 24 h.
[0023] The second aspect of the present invention provides a neutral silver-zinc battery positive electrode material, wherein the positive electrode material is prepared by the preparation method described in the present invention.
[0024] The third aspect of the present invention provides a neutral silver-zinc battery, which at least includes the neutral silver-zinc battery positive electrode material described in the present invention.
[0025] Beneficial effect: The preparation method of the present invention comprises the steps of: x Mixed with chloroauric acid solution, on Ti3C2T x The surface is modified with gold nanoclusters and then reacted with silver nitrate / sodium citrate solution to form Ti3C2T3 with gold nanoclusters attached to the surface. x Silver nanoparticles are formed on the surface, and a large number of Au-Ag nanoparticles (referring to Au nanoparticles and Ag nanoparticles) are attached to the surface of Ti3C2T xThe composite material is then coated with a large amount of Au-Ag nanoparticles on the surface of the obtained Ti3C2T x The composite material is compounded with carbon nanotube dispersion and melamine to obtain Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material. The electrode material of the present invention can effectively inhibit the migration of silver ions, ensure a high cycle life, and inhibit the agglomeration of silver nanoparticles, thereby maintaining a large number of small-sized silver nanoparticles. The obtained small-sized silver nanoparticles provide sufficient active sites for the rapid electrochemical reaction of the battery, and the conductive framework without polymer binder provides an ideal specific capacity and rate performance for the neutral silver-zinc battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The Ti3C2T prepared in Example 1 has a large amount of Au-Ag nanoparticles attached to its surface. x Melamine positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached on the surface x Melamine positive electrode material and Ti3C2T with a large amount of Ag nanoparticles attached on the surface x CV curve of positive electrode material;
[0027] Figure 2 They are Ti3C2T with a large number of Ag nanoparticles attached to the surface. x Positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached to the surface x Melamine positive electrode material and Ti3C2T with a large amount of Au-Ag nanoparticles attached on the surface x SEM images of the positive electrode of the neutral silver-zinc battery assembled with melamine positive electrode material after 100 cycles;
[0028] Figure 3 Ag nanoparticles Ti3C2T x Positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached to the surface x SEM images of the separator of the neutral silver-zinc battery assembled with melamine positive electrode material after 50 cycles;
[0029] Figure 4 The prepared Ti3C2T x Melamine positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached on the surface x Melamine positive electrode material and Ti3C2T with a large amount of Ag nanoparticles attached on the surface x The rate performance of neutral silver-zinc batteries assembled with positive electrode materials;
[0030] Figure 5The Ti3C2T prepared in Example 1 has a large amount of Au-Ag nanoparticles attached to its surface. x Cycling performance of neutral silver-zinc batteries assembled with melamine positive electrode materials. DETAILED DESCRIPTION
[0031] The present invention provides a neutral silver-zinc battery positive electrode material and a preparation method thereof and a neutral silver-zinc battery. In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] The performance of neutral silver-zinc batteries mainly depends on the positive electrode material. MXene has unique advantages such as large specific surface area, high flexibility, and high conductivity, and is widely used in the field of energy storage. x As the first discovered MXene material, it not only has the advantages of large specific surface area and short diffusion path, but also has excellent conductivity. It is an ideal electrode material for the development of high-rate, large-capacity supercapacitors, ion batteries and other energy storage devices.
[0033] Specifically, the method for preparing the neutral silver-zinc battery positive electrode material of the embodiment of the present invention comprises the steps of:
[0034] S1. Add chloroauric acid solution to Ti3C2T x The Ti3C2T with gold nanoclusters attached to the surface was obtained by reaction in solution. x Solution.
[0035] Although the neutral silver-zinc battery has a high cycle life, the rate performance of the neutral silver-zinc battery is unsatisfactory due to the agglomeration of silver nanoparticles and the low conductivity of AgCl. x In solution, gold nanoclusters, as an efficient interfacial charge transfer medium, can significantly accelerate charge transfer, thereby effectively improving the kinetics and reversibility of the electrochemical process, thereby improving the battery's cycle stability and rate performance. In addition, Ag and Au belong to the same family and have similar crystal structures, and Au has higher stability than Ag and is almost insoluble in water, which can provide a more stable attachment point for silver nanoparticles and effectively inhibit the agglomeration of silver nanoparticles, thereby improving the capacity attenuation problem at the beginning of the battery cycle.
[0036] In specific implementation, if the mixed solution of silver nitrate solution and sodium citrate is directly added to Ti3C2T x solution, the Ti3C2T obtained in the subsequent step x @Ag (refers to Ti3C2T with silver nanoparticles attached to the surface x), silver nanoparticles will rapidly aggregate during the initial charge and discharge process, which will lead to a rapid reduction in the active surface area that can participate in the reaction, resulting in a rapid decline in the battery capacity. x Solution reaction, Ti3C2T x Loading a certain amount of gold nanoclusters on the surface can effectively inhibit the agglomeration of silver nanoparticles and improve the kinetics and reversibility of the electrochemical process, thereby significantly improving the cycle stability of neutral silver-zinc batteries.
[0037] Furthermore, in order to make the gold nanoclusters evenly distributed on the Ti3C2T x In this embodiment, chloroauric acid solution is added to Ti3C2T x After the solution is prepared, the mixed solution is placed in an ice water bath and reacted under stirring to make the mixed solution fully mixed. In this embodiment, a Ti3C2T3O ... x The temperature of the ice water bath is 1°C to 15°C, the reaction time is more than 1 hour, and further the reaction time is 1 to 4 hours.
[0038] Preferably, chloroauric acid and Ti3C2T x The mass ratio of chloroauric acid to Ti3C2T x When the dosage is too low, the silver nanoparticles will aggregate to varying degrees during the subsequent charge and discharge process, resulting in a decrease in the battery specific capacity. x When the mass ratio is 0.2-0.3:1, that is, the amount of chloroauric acid added is greater than 5wt% of the silver nanoparticles, the initial capacity retention rate of the neutral silver-zinc battery is greatly improved. When the amount of chloroauric acid is too high, a large number of gold nanoclusters cannot provide capacity, resulting in a decrease in the energy density of the neutral silver-zinc battery.
[0039] S2, adding a mixed solution of silver nitrate solution and sodium citrate to the Ti3C2T x After the reaction, Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface was obtained. x Composite materials.
[0040] In specific implementation, by adjusting the ratio of silver nitrate to sodium citrate, the size of silver nanoparticles is controlled to provide more active surfaces that can participate in the reaction, thereby improving the specific capacity of the neutral silver-zinc battery. Preferably, in the mixed solution of silver nitrate solution and sodium citrate in this embodiment, the molar ratio of silver nitrate solution to sodium citrate is 1:2 to 1:7, and the molar ratio of silver nitrate to Ti3C2T x The mass ratio is 0.7~1.8:1.
[0041] In a specific implementation, in order to obtain a neutral silver-zinc battery with a long cycle life and the desired rate performance, in this embodiment, a mixed solution of silver nitrate solution and sodium citrate is further added to the Ti3C2T4O ... x The reaction was continued for more than 4 hours to make Ti3C2T x Au-Ag nanoparticles are formed on the surface. The mixed solution after the reaction is then washed several times with deionized water to remove a small amount of impurities in the mixed solution, and a Ti3C2T3 with a large number of Au-Ag nanoparticles attached to the surface is obtained. x Composite materials.
[0042] S3, the Ti3C2T x The composite material is mixed with a carbon nanotube dispersion (the dispersant may be an alcohol, such as ethanol) and melamine, and then vacuum filtered to obtain a Ti3C2T3 with Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material.
[0043] Preferably, melamine and Ti3C2T3 with a large amount of Au-Ag nanoparticles attached to the surface x The mass ratio of the composite material is 0.3-0.7:1, and melamine can increase the positive electrode's affinity to Ag. + The adsorption capacity can effectively inhibit Ag + The migration phenomenon of the neutral silver-zinc battery is improved, thereby improving the cycle life of the neutral silver-zinc battery. However, melamine does not provide capacity. When too much melamine is added, the battery specific capacity will decrease. More preferably, the amount of melamine added in this embodiment is Ti3C2T x When the content of the composite material is 70wt%, the cycle stability of the neutral silver-zinc battery can be more effectively improved.
[0044] In order to further improve the Ti3C2T x The contact surface between the melamine positive electrode material and the electrolyte, in this embodiment, the Ti3C2T x The melamine positive electrode material is further compounded with carbon nanotubes, and Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface is obtained by filtration and drying. x Melamine positive electrode material, thereby giving the positive electrode material better mechanical properties.
[0045] Since carbon nanotubes cannot provide capacity, in specific implementation, as the specific gravity of carbon nanotubes increases, the active material loading is low, and sufficient electrochemical reaction sites cannot be provided, which ultimately causes a decrease in specific capacity; and as the specific gravity of carbon nanotubes decreases, the flexibility of the positive electrode also decreases, resulting in insufficient mechanical strength of the positive electrode. Preferably, in this embodiment, the carbon nanotubes and the Ti3C2T4 with a large number of Au-Ag nanoparticles attached to the surface x The mass ratio of the melamine composite material is 0.3 to 1:1. Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface is obtained by drying in an oven. x Melamine positive electrode material, wherein drying is performed at 60° C. to 80° C. for 12 h to 24 h.
[0046] In another embodiment, the present invention further provides a neutral silver-zinc battery positive electrode material, wherein the positive electrode material is prepared by the preparation method described in the embodiment of the present invention.
[0047] In another embodiment, the present invention also provides a neutral silver-zinc battery, wherein the neutral silver-zinc battery comprises the neutral silver-zinc battery positive electrode material of the embodiment of the present invention, that is, the Ti3C2T400 having Au-Ag nanoparticles attached to the surface of the above-mentioned positive electrode material. x Melamine positive electrode material.
[0048] In a specific embodiment of the present invention, the preparation method of the neutral silver-zinc battery comprises the steps of: preparing a Ti3C2T3O4 battery having a large amount of Au-Ag nanoparticles attached to the surface prepared in the above steps; x The melamine positive electrode material, the separator, the ZnCl2 electrolyte, and the zinc negative electrode are assembled into a neutral silver-zinc battery. Specifically, the concentration of the electrolyte can be set as needed. In a specific embodiment, the concentration of the ZnCl2 electrolyte is 0.05 mol / L to 5 mol / L.
[0049] The present invention is based on Ti3C2T x The gold nanoclusters were introduced into the Ti3C2T4O3O4 ... x In the solution, silver nanoparticles are used as crystal nuclei of gold nanoclusters to form Au-Ag nanoparticles; finally, the Ti3C2T x The composite material is compounded with carbon nanotubes and melamine to obtain Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface, which has high mechanical strength, high rate performance and stable cycle performance. x Melamine positive electrode material.
[0050] The present invention is further explained below by means of specific embodiments.
[0051] Example 1
[0052] (1) Dissolve 0.8 mg of chloroauric acid in 5 mL of deionized water and add it to 50 mL of Ti3C2T x The solution was then placed in an ice-water bath at 5°C for 1 h to obtain Ti3C2T3 with gold nanoclusters attached to the surface. x Solution;
[0053] (2) 15 mg of silver nitrate and 5 mg of sodium citrate were dissolved in 9 mL of deionized water and added to the Ti3C2T4 x The solution was placed in a 5°C ice water bath and stirred for 4 h. After a predetermined time, the mixture was washed several times with deionized water and the supernatant was removed to obtain a Ti3C2T3O4 with a large amount of Au-Ag nanoparticles attached to the surface. x Composite materials.
[0054] (3) Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface x Melamine and carbon nanotube ethanol dispersion were added to the composite material in sequence, stirred for 10 min, and vacuum-assisted filtration was performed. The filtered material was placed in an oven at 60 °C and dried for 12 h to obtain Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material;
[0055] (4) Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface x Melamine positive electrode material is used as the positive electrode, zinc foil is used as the negative electrode, and ZnCl2 is used as the electrolyte to obtain a neutral silver-zinc battery.
[0056] Example 2
[0057] This embodiment is substantially the same as embodiment 1, except that the amount of chloroauric acid used in step (1) is 0 mg.
[0058] Example 3
[0059] This embodiment is substantially the same as embodiment 1, except that the amount of chloroauric acid used in step (1) is 0 mg, and the amount of melamine added in step (4) is 0 mg.
[0060] Figure 1 They are Ti3C2T3 prepared in Examples 1, 2, and 3 with a large amount of Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached on the surface xMelamine positive electrode material and Ti3C2T with a large amount of Ag nanoparticles attached on the surface x CV curve of positive electrode material. Figure 1 From the closed area of the CV curve, it can be found that the addition of gold nanoclusters can effectively reduce the peak position difference of the redox peak, which indicates that the addition of gold nanoclusters can improve the electrochemical kinetics of neutral silver-zinc batteries.
[0061] Figure 2 They are Ti3C2T with a large number of Ag nanoparticles attached to the surface. x Positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached to the surface x Melamine positive electrode material and Ti3C2T with a large amount of Au-Ag nanoparticles attached on the surface x SEM images of the positive electrode of the neutral silver-zinc battery assembled with melamine positive electrode material after 100 cycles. Figure 2 It can be seen that by introducing gold nanoclusters as the crystal nuclei of silver nanoparticles, the agglomeration of silver nanoparticles can be effectively inhibited, and as many active surfaces that can participate in the reaction as possible can be maintained, thereby providing higher cycle stability.
[0062] Figure 3 It is Ti3C2T with a large number of Ag nanoparticles attached to the surface x Positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached to the surface x SEM images of the separator of the neutral silver-zinc battery assembled with melamine positive electrode material after 50 cycles. Figure 3 It can be seen that by introducing melamine into the positive electrode, the migration behavior of silver ions under the action of the electric field can be inhibited, thereby effectively preventing the silver particles in the diaphragm from piercing the diaphragm and causing a short circuit, thereby greatly improving the cycle life of the neutral silver-zinc battery.
[0063] Figure 4 They are Ti3C2T3 prepared in Examples 1, 2, and 3 with a large amount of Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material, Ti3C2T with a large amount of Ag nanoparticles attached on the surface x Melamine positive electrode material and Ti3C2T with a large amount of Ag nanoparticles attached on the surface x The rate performance of neutral silver-zinc batteries assembled with positive electrode materials. Figure 4 It can be seen that the introduction of melamine and gold nanoclusters into the positive electrode can effectively improve the rate performance and capacity retention of neutral silver-zinc batteries.
[0064] Figure 5 The Ti3C2T prepared in Example 1 has a large amount of Au-Ag nanoparticles attached to its surface. x The cycling performance of neutral silver-zinc batteries assembled with melamine positive electrode materials is determined by Figure 5 It can be seen that the battery has a cycle life of more than 9000 times, indicating that melamine and gold nanoclusters can significantly improve the cycle stability of neutral silver-zinc batteries.
[0065] In summary, the present invention discloses a neutral silver-zinc battery positive electrode material and a preparation method thereof and a neutral silver-zinc battery. The preparation method comprises adding chloroauric acid to Ti3C2T x The solution was fully reacted to obtain Ti3C2T with gold nanoclusters attached on the surface. x solution; adding a mixed solution of silver nitrate and sodium citrate to the solution, and after reaction, obtaining a Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface x Composite material; Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface x The composite material was added with melamine and carbon nanotube dispersion and stirred thoroughly, and vacuum-assisted filtration and drying were performed to obtain Ti3C2T with a large amount of Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material. The neutral silver-zinc battery positive electrode material prepared by the present invention uses gold nanoclusters as the crystal nuclei of silver nanoparticles, which can effectively inhibit the agglomeration of silver nanoparticles; at the same time, the melamine added to the positive electrode can effectively inhibit the migration of silver ions and effectively improve the cycle stability of the neutral silver-zinc battery.
[0066] The neutral silver-zinc battery positive electrode material prepared by the present invention has a conductive framework structure stacked on each other, which can ensure the transmission capacity of electrons and ions, as well as mechanical stability; the obtained small-sized silver nanoparticles provide sufficient active sites for the rapid electrochemical reaction of the battery, and the conductive framework without polymer binder provides an ideal specific capacity and rate performance for the neutral silver-zinc battery.
[0067] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a neutral silver-zinc battery positive electrode material, characterized in that: Includes steps: Add chloroauric acid solution to Ti3C2T x The Ti3C2T with gold nanoclusters attached to the surface was obtained by reaction in solution. x Solution; A mixed solution of silver nitrate solution and sodium citrate is added to the Ti3C2T x After the reaction, Ti3C2T with Au-Ag nanoparticles attached to the surface was obtained. x Composite materials; The Ti3C2T x The composite material was mixed with carbon nanotube dispersion and melamine, and then vacuum filtered to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material.
2. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 1, characterized in that: The chloroauric acid solution is added to the Ti3C2T x The Ti3C2T with gold nanoclusters attached to the surface was obtained by reaction in solution. x The solution steps include: Add chloroauric acid solution to Ti3C2T x The solution was placed in an ice water bath and reacted under stirring to obtain Ti3C2T with gold nanoclusters attached to the surface. x Solution; Wherein, the temperature of the ice water bath is 1°C to 15°C, and the reaction time is more than 1 hour.
3. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 1, characterized in that: The chloroauric acid, the Ti3C2T x The mass ratio is 0.01~0.3:
1.
4. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 1, characterized in that: A mixed solution of silver nitrate solution and sodium citrate is added to the Ti3C2T x After the reaction, Ti3C2T with Au-Ag nanoparticles attached to the surface was obtained. x The steps of composite material include: A mixed solution of silver nitrate solution and sodium citrate is added to the Ti3C2T x The reaction was continued for more than 4 h to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x Composite materials.
5. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 1, characterized in that: The molar ratio of the silver nitrate solution to the sodium citrate in the mixed solution of the silver nitrate solution and the sodium citrate is 1:2 to 1:7, and the molar ratio of the silver nitrate to the Ti3C2T x The mass ratio is 0.7~1.8:
1.
6. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 1, characterized in that: The Ti3C2T x The composite material was mixed with carbon nanotube dispersion and melamine, and then vacuum filtered to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x The steps of melamine cathode material include: The Ti3C2T with Au-Ag nanoparticles attached on the surface x The carbon nanotube dispersion and melamine were added to the composite material, stirred, vacuum filtered, and dried to obtain Ti3C2T with Au-Ag nanoparticles attached to the surface. x Melamine positive electrode material.
7. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 1, characterized in that: The melamine and the Ti3C2T x The mass ratio of the composite material is 0.3-0.7:1, and the carbon nanotubes and the Ti3C2T x The mass ratio of the composite material is 0.3 to 1:
1.
8. The method for preparing a neutral silver-zinc battery positive electrode material according to claim 6, characterized in that: The drying is specifically: drying at 60° C. to 80° C. for 12 h to 24 h.
9. A neutral silver-zinc battery positive electrode material, characterized in that: The preparation method is as described in any one of claims 1 to 8.
10. A neutral silver-zinc battery, characterized in that: At least comprises the neutral silver-zinc battery positive electrode material as claimed in claim 9.
